Examining Competitive Strategies in Growing Coffee Industry with Game Theory - Hüseyin Daştan; Gürkan Çalmaşur; Meryem Aysin; Fatmanur Oral (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The coffee market in Turkey is growing rapidly, leading to fierce competition between international, national and local coffee shops. It has become extremely important for the local economy that local businesses can compete and survive with these more institutionalized structures that also have brand advantages in competition. In this study, game theory was used as a tool to analyse the competitive strategies of companies operating in the coffee market by designing both zero-sum and non-zero-sum games. Considering that the expectations, tastes, preferences and consumption habits of the generations may be different, 1600 people were surveyed in Erzurum province by grouping them as Generation X, Y and Z according to their year of birth. Different game matrices were created with the data obtained from the surveys. The games were designed to identify the prominent strategies among coffee shops for each generation. The results showed that, regardless of generation, local coffee shops stand out from international and national coffee chains in terms of space comfort. In addition, local shops also stand out in terms of meeting consumer expectations. In order to gain a competitive advantage, local coffee shops should focus on developing strategies related to the space comfort. Developing this strategy provides opportunities for local businesses to increase their market share. It is also observed that Generation Z has higher expectations in all strategies compared to other generations.